Pulsed-dye laser efficacy in the treatment of psoriasis in adult patients: An evidence-based case report - Krisna, Made Ananda; Nilasari, Hanny (Journal of General - Procedural Dermatology and Venereology Indonesia, 2016)
Psoriasis is a chronic inflammatory skin disease known to be highly responsive to phototherapy. Narrow-band UVB (NBUVB) phototherapy has been one of the standard treatments for its moderate to severe form. However, its lack of efficacy in treating stable psoriatic plaques on extremities has lead researchers to find alternative treatments, one of which is pulsed-dye laser (PDL). Laser has been known to be effective in treating vascular lesions; in psoriasis, elongation of rete ridge along with tortuous dermal capillaries are one of the first pathologies identified early in the disease progression. Several in vivo and preliminary studies have found the molecular mechanism of action of laser on abnormal vessel growth. In this article, we report a psoriasis vulgaris case in adult whose lesions responded well to NBUVB phototherapy. The psoriatic plaques on her extremities were stable despite NBUVB therapy and some topical treatments afterwards. With knowledge of emerging role of PDL in inflammatory skin disease such as psoriasis, we conducted a literature search and critically appraised the resulting articles. The systematic review article found evaluates PDL efficacy as a treatment for inflammatory skin diseases, including psoriasis, and was appraised using a worksheet from British Medical Journal Evidence-Based Medicine Toolkit. Its validity, importance, and applicability aspects were evaluated, leading to a conclusion that PDL can be used as an alternative treatment for psoriasis plaques in trunks, extremities, hands, or feet (both stable and unstable), with minimal and transient side effects (hyperpigmentation, hypopigmentation, and blistering).